The Modified Trial Equation Method for Fractional Wave Equation and Time Fractional Generalized Burgers Equation - Bulut, Hasan; Baskonus, Haci Mehmet; Pandir, Yusuf (Hindawi Ltd, 2013)
The fractional partial differential equations stand for natural phenomena all over the world from science to engineering. When it comes to obtaining the solutions of these equations, there are many various techniques in the literature. Some of these give to us approximate solutions; others give to us analytical solutions. In this paper, we applied the modified trial equation method (MTEM) to the one-dimensional nonlinear fractional wave equation (FWE) and time fractional generalized Burgers equation. Then, we submitted 3D graphics for different value of alpha.
Keywords: Diffusion